2024
DOI: 10.37113/ideaj.vi0.192
|View full text |Cite
|
Sign up to set email alerts
|

Chaos, Territory, Art. Deleuze and the Framing of the Earth

Abstract: This paper is about the ontology, the materiality and logical structure of art. While I am not trained in the visual arts or architecture, nonetheless I see there are many points of overlap, regions of co-occupation, that concern art and philosophy, and it is these shared concerns that I want to explore. I want to discuss the ‘origins’ of art and architecture, but not the historical, evolutionary or material origins of art – an origin confirmable by some kind of material evidence or resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
150
0
5

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(155 citation statements)
references
References 2 publications
0
150
0
5
Order By: Relevance
“…While Deleuze and Guattari's work 'is not political philosophy in the sense that it provides tools for the justification or critique of political institutions and processes, … it is a political ontology that provides tools to describe transformative, creative or deterritorializing forces and movements' (Patton 2000, 9). As such, it has sparked interest with political philosophers (Bennett 2010;Connolly 2011;DeLanda 2006;Grosz 2008;Protevi 2009), but also lately with political geographers, who have appreciated it for its concern with materiality and new ways of conceptualising power and space.…”
Section: Assemblagementioning
confidence: 99%
“…While Deleuze and Guattari's work 'is not political philosophy in the sense that it provides tools for the justification or critique of political institutions and processes, … it is a political ontology that provides tools to describe transformative, creative or deterritorializing forces and movements' (Patton 2000, 9). As such, it has sparked interest with political philosophers (Bennett 2010;Connolly 2011;DeLanda 2006;Grosz 2008;Protevi 2009), but also lately with political geographers, who have appreciated it for its concern with materiality and new ways of conceptualising power and space.…”
Section: Assemblagementioning
confidence: 99%
“…Icelanders at the Fimmvörðuháls eruption site said that they simply had to witness the spectacleand this was also backed up in some of the survey responses: there is something human in meeting with the inhuman (Clark, 2011). This paper has suggested that an important aspect of understanding the geosocial might be around its commodification, through experiences of active and dynamic landscapes as well as through art and culture (Dixon et al, 2013;Grosz, 2008;Yusoff et al, 2012): people are drawn to the sensory and imaginative, knowledge-generating spectacles of volcanic eruptions because of their affective and personal effects. Such encounters enrich curiosityseveral survey respondents stated that the eruption in 2010 had inspired them to study geoscienceand they change the way that people thinkin a sense consistent both with Deleuze and with notions of the sublime as simultaneously showing mental limits and pointing beyond them.…”
Section: Resultsmentioning
confidence: 96%
“…Thus, while affect is much broader than the sublime, it can encompass at least some of the interpretations of the sublime discussed above. Grosz (2008) and Deleuze and Guattari, in bringing together the "vast planes" of art, science and philosophy as different ways of addressing the universe at the "junction" of the brain (Deleuze, 1994;Deleuze & Guattari, 1988), also suggest that the planes can cooperate by working across their commonalities. Such working presents huge opportunities for cross-disciplinary working to reduce risk while also respecting indigenous and non-scientific values and knowledges.…”
Section: Sublime Affectsmentioning
confidence: 99%
“…Rather, it is how such materials transgress thresholds of "human" and "non-human" to trouble their known quality and in doing so, produce new subjectivities and micro-groupings (Grosz, 2005). The philosophical trajectories recovered and developed by Deleuze and Guattari (1987) and Grosz (2001Grosz ( , 2008, among others, provide many examples of such micro-groupings that raise important questions about urban tactics in the post-political era. Of particular relevance is the relationship this literature draws between the ontological diversity of the more-than-human and the creation of what Grosz (1999) refers to as the truly new.…”
Section: Assemblage and Ontological Diversitymentioning
confidence: 99%